Electrocatalyst, preparation and application thereof, and biomass-derived aldehyde fuel cell for co-production of electric energy and hydrogen

By preparing specific electrocatalysts, using biomass-derived aldehyde fuel cells to achieve efficient hydrogen production and electrical energy output at room temperature, solving the problems of slow anode reaction kinetics and high energy consumption in the prior art, and achieving efficient and safe hydrogen gas Production.

CN119133472AActive Publication Date: 2024-12-13GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411210668.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

In the existing electrolytic water hydrogen production technology, the redox reaction kinetics of the anode are slow, resulting in high electricity cost for hydrogen production and low added value of oxygen generated by the anode, limiting the commercial application of the biomass oxidation coupled cathode hydrogen production technology.

Method used

Using an electrocatalyst preparation method, copper, silver and gold nanoparticles are activated by electrodeposition and cyclic voltammetry to form supported metal oxide nanoparticles, and a cogeneration electric energy is prepared by doping metal elements. A biomass-derived aldehyde fuel cell of hydrogen gas uses biomass-derived aldehyde oxidation to generate carboxylic acid compounds and hydrogen gas.

Benefits of technology

Achieve high output power density (173.5mW/cm2) and fast hydrogen production rate (1.96mmol/cm2/h) at room temperature, reducing hydrogen production energy consumption, and improving Faraday efficiency, with high safety and economical sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133472A_ABST
    Figure CN119133472A_ABST
Patent Text Reader

Abstract

The invention discloses an electrocatalyst, preparation and application thereof, and a biomass derived aldehyde fuel cell for co-production of electric energy and hydrogen. The invention particularly relates to preparation of an electrocatalyst for efficiently catalyzing oxidation of aldehyde groups to produce hydrogen and construction of a biomass derived aldehyde fuel cell capable of synchronously producing electric energy and hydrogen. The battery realizes higher output power density (173.5 mW / cm < 2 >), higher Faraday efficiency (close to 100%) and higher hydrogen production rate (1.96 mmol / cm < 2 > / h) at room temperature, and is at a leading level in the existing research. Besides, during power generation, biomass derived aldehyde of the anode is oxidized into corresponding carboxylic acid compounds, the process is carried out at room temperature and normal pressure, the reaction is flexible and controllable, and compared with a traditional aldehyde oxidation technology, the method has higher safety and economical efficiency. The method has a wide application prospect in the fields of power generation, hydrogen production, biomass conversion and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomass chemical industry, and specifically relates to an electrocatalyst and its preparation, application and biomass-derived aldehyde fuel cell for co-producing electricity and hydrogen. Background Art

[0002] Hydrogen energy is an important part of the future national energy system and can be used in oil refining, hydrogenation, synthetic ammonia / methanol, hydrogen fuel cells, hydrogen metallurgy and other fields. In China, the annual output of hydrogen is increasing year by year, but most of the hydrogen comes from fossil energy, which will emit a lot of carbon dioxide during the preparation process and consume non-renewable resources such as coal and natural gas, which is contrary to the concept of sustainable development. Therefore, it is urgent to develop green hydrogen production technology based on renewable energy.

[0003] Hydrogen production by water electrolysis is a green and safe hydrogen production technology, which consists of two half-reactions: the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). An important reason restricting the development of hydrogen production by water electrolysis is that the OER kinetics at the anode are slow and the overpotential is high, which greatly increases the electricity cost of hydrogen production, and the added value of the oxygen produced at the anode is low. In recent years, some researchers have used the oxidation reactions of various biomass and its derivatives (organic substrates) to replace OER, which can reduce the overpotential of the anode reaction, slightly reduce the energy consumption of hydrogen production, and produce some chemicals with high added value. Zhou et al. (Angew. Chem. Int. Ed. 2021, 60, 8976-8982) used manganese-doped cobalt hydroxide (MnCoOOH) anode catalyst to selectively electrocatalytically convert lignin derivatives into carboxylates, and at the same time coupled the cathode HER, at 1.5V. RHE The hydrogen production rate at the potential of 1.41mmol / cm 2 Cui et al. (J.Am.Chem.Soc.2021,143,9429-9439) used nitrogen-doped carbon nanotubes (Pt1 / N-CNTs) with atomically dispersed Pt-N3C1 active sites to electrocatalyze the cleavage of C in lignin model compounds. α -C β Miao et al. (Appl. Catal., B, 2023, 336, 122937) used Ir single-atom electrocatalyst (Ir-NiFeO@NF) to electrocatalyze the conversion of lignocellulose into carboxylic acid and coupled the cathode HER at the same time. The hydrogen production rate was 0.45 mmol / cm at an applied voltage of 1.5 V. 2 / h.

[0004] Although the technology of anode biomass oxidation coupled to cathode hydrogen production has been developed to a certain extent, compared with the traditional complete water splitting reaction, this system can only slightly reduce the power consumption, and the applied voltage is usually greater than 1.5V, which still consumes a lot of power, seriously restricting its commercial application. Therefore, it is urgent to develop a new technology for hydrogen production that is more energy-efficient. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing an electrocatalyst.

[0006] Another object of the present invention is to provide an electrocatalyst prepared by the above preparation method.

[0007] Another object of the present invention is to provide application of the above-mentioned electrocatalyst in a fuel cell.

[0008] Another object of the present invention is to provide a biomass-derived aldehyde fuel cell that co-generates electricity and hydrogen.

[0009] The fuel cell provided by the present invention can oxidize biomass-derived aldehydes into carboxylic acid compounds and generate electricity and hydrogen at the same time. Compared with the traditional hydrogen production by water electrolysis, the present invention is an electrocatalytic hydrogen production system that does not require electricity input and can output electricity to the outside, greatly reducing the energy consumption of hydrogen production. In addition, the biomass-derived aldehyde fuel cell of the present invention can operate at room temperature (25°C) and has a high output power density (173.5mW / cm 2 ) and a faster hydrogen production rate (1.96mmol / cm 2 / h). The present invention has good universality and broad application prospects in the fields of power generation, hydrogen production, and biomass conversion. Various biomass-derived aldehydes (including benzaldehyde, furfural, p-methoxybenzaldehyde, 3,4-dimethoxybenzaldehyde, etc.) can be used in the fuel cell of the present invention to achieve power generation and hydrogen production at the same time.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] A method for preparing an electrocatalyst comprises the following steps:

[0012] (1) preparing at least one of copper, silver and gold nanoparticles on a substrate by electrodeposition to obtain a substrate loaded with nanoparticles;

[0013] (2) activating the substrate loaded with nanoparticles in step (1) by cyclic voltammetry (CV), and then performing electrochemical reduction or reducing agent reduction to obtain a substrate loaded with metal oxide nanoparticles;

[0014] The metal oxide nanoparticles are metal oxides corresponding to at least one element of copper, silver and gold;

[0015] (3) doping the substrate loaded with metal oxide nanoparticles in step (2) with metal elements and then performing electrochemical reduction or reducing agent reduction to obtain a substrate loaded with metal elements doped with metal oxide nanoparticles, i.e., an electrocatalyst;

[0016] The metal element doped therein is different from the metal element in the metal oxide nanoparticles.

[0017] Preferably, the substrate in step (1) is at least one of foamed copper, foamed nickel, foamed zinc, foamed aluminum, carbon felt, carbon paper and carbon cloth.

[0018] Preferably, in step (1), the substrate is washed with acetone, hydrochloric acid solution, anhydrous ethanol and water in sequence before electrodeposition, and the washing method is ultrasonic washing.

[0019] Preferably, the electrolyte used in the electrodeposition method in step (1) is at least one of CuSO4, CuCl2, Cu(NO3)2, AgNO3 and AuBr3, with a concentration of 0.01 to 3 mol / L.

[0020] More preferably, the electrolyte further contains 0.001-2 mol / L ethanol and 0.001-4 mol / L H2SO4.

[0021] Preferably, the electrodeposition process in step (1) is carried out in a three-electrode system, wherein the constant current is -500 to -1 mA / cm 2 The electrodeposition time is 10 to 5000 s.

[0022] More preferably, the working electrode of the three-electrode system is the substrate described in step (1), the reference electrode is Ag / AgCl, and the counter electrode is a graphite rod.

[0023] Preferably, the cyclic voltammetry activation in step (2) is performed in a three-electrode system with a scanning range of -1.0 to 2.0 V. RHE , the scanning speed is 0.5~100mV / s, and the cycle is 1~100 times.

[0024] More preferably, the working electrode of the three-electrode system is the substrate loaded with nanoparticles in step (1), the reference electrode is Hg / HgO, and the counter electrode is a graphite rod.

[0025] Preferably, the electrolyte activated by cyclic voltammetry in step (2) is at least one of KOH, NaOH, Na2CO3, NaHCO3, K2CO3 and KHCO3, with a concentration of 0.05 to 5 mol / L.

[0026] Preferably, the electrochemical reduction in step (2) is carried out in a three-electrode system activated by cyclic voltammetry, wherein the constant potential is -3.0 to 0.4 V. RHE , the restoration time is 10 to 3600s.

[0027] Preferably, the reducing agent in step (2) is at least one of NaBH4, LiBH4 and Zn(BH4)2; specifically, the substrate loaded with nanoparticles after cyclic voltammetry activation is placed in a 0.001-3 mol / L reducing agent aqueous solution for immersion reduction, and the reduction time is 10-5000 s.

[0028] Preferably, the method of doping with the metal element in step (3) is: placing the substrate loaded with metal oxide nanoparticles in a 0.05-50 mmol / L metal salt solution for 10-240 min; and doping the metal element into the metal oxide nanoparticles.

[0029] More preferably, the metal salt solution is at least one of AgNO3, RuCl3, AuBr3, PdCl2, Pt(NO3)2, Fe(NO3)3 and Co(NO3)2.

[0030] Preferably, the doped metal element in step (3) is at least one of Ag, Ru, Au, Pd, Pt, Fe and Co.

[0031] Preferably, the electrochemical reduction in step (3) is carried out in a three-electrode system at a constant potential of -3.0 to 0.4 V. RHE , the restoration time is 10 to 3600s.

[0032] More preferably, the electrolyte of the three-electrode system is at least one of KOH, NaOH, Na2CO3, NaHCO3, K2CO3 and KHCO3, with a concentration of 0.05 to 5 mol / L; the working electrode is a loaded metal oxide nanoparticle substrate after soaking in a metal salt solution, the reference electrode is Hg / HgO, and the counter electrode is a graphite rod.

[0033] Preferably, the reducing agent in step (3) is at least one of NaBH4, LiBH4 and Zn(BH4)2. The electrocatalyst precursor to be reduced is placed in a 0.001-3 mol / L reducing agent aqueous solution for immersion reduction, and the reduction time is 10-3600 s.

[0034] An electrocatalyst prepared by the above preparation method.

[0035] Application of the above-mentioned electrocatalyst in a fuel cell.

[0036] A biomass-derived aldehyde fuel cell for co-producing electricity and hydrogen comprises an anode, a cathode, an anolyte, a cathode electrolyte, a diaphragm and a conductor; wherein the anode is loaded with the above-mentioned electrocatalyst; and the anolyte contains a biomass-derived aldehyde at a concentration of 1 to 1000 mmol / L.

[0037] Preferably, the anode and cathode of the biomass-derived aldehyde fuel cell are separated by a diaphragm to form an anode chamber filled with an anode electrolyte and a cathode chamber filled with a cathode electrolyte.

[0038] Preferably, the membrane is a Nafion membrane.

[0039] Preferably, the biomass-derived aldehyde fuel cell further comprises a circulation pump, through which the anolyte and the cathode electrolyte are continuously replenished into the anode electrolytic cell and the cathode electrolytic cell respectively.

[0040] Preferably, the wires connect the anode and cathode to an external circuit respectively, that is, the battery anode is connected to an external load, and the battery cathode is connected to an external load.

[0041] Preferably, the electrode material in the cathode is carbon felt.

[0042] Preferably, the biomass-derived aldehyde in the anolyte is at least one of benzaldehyde, p-anisaldehyde, 3,4-dimethoxybenzaldehyde, furfural, 5-hydroxymethylfurfural and formaldehyde.

[0043] Preferably, the concentration of the biomass-derived aldehyde in the anolyte is 1 to 1000 mmol / L, more preferably 10 to 500 mmol / L, most preferably 30 to 200 mmol / L.

[0044] Preferably, the alkali in the anolyte is at least one of NaOH, KOH and ammonia water, and the concentration of the alkali is 0.001 to 8 mol / L, more preferably 0.1 to 4 mol / L, and most preferably 1 to 2 mol / L.

[0045] Preferably, the operating temperature of the biomass-derived aldehyde fuel cell is 5 to 98°C.

[0046] Preferably, the cathode electrolyte comprises a ferric iron salt with a concentration of 0.01 to 4 mol / L, an acid solution with a concentration of 0.01 to 6 mol / L, and a cathode regeneration oxidant.

[0047] More preferably, the trivalent iron salt is at least one of ferric chloride, ferric sulfate and ferric nitrate; the acid solution is at least one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution; and the cathode regeneration oxidant is at least one of nitric acid, oxygen, hydrogen peroxide and potassium permanganate.

[0048] Further preferably, when the cathode regeneration oxidant is nitric acid, its concentration in the cathode electrolyte is 0.01 to 8 mol / L; when the cathode regeneration oxidant is oxygen, its flow rate is 10 to 100 mL / min; when the cathode regeneration oxidant is hydrogen peroxide, its concentration is 0.2 to 10 mol / L; when the cathode regeneration oxidant is potassium permanganate, its concentration is 0.01 to 0.5 mol / L.

[0049] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0050] 1. The present invention uses the prepared electrocatalyst to construct a biomass-derived aldehyde fuel cell, transforming the power-consuming process of electrocatalytic hydrogen production into a power generation process; 3+ Reduction to Fe 2+ The reaction is coupled to realize the spontaneous and rapid transfer of electrons from the anode to the cathode, and output electrical energy to the outside. While generating electrical energy, the aldehyde group of the anode will release hydrogen after oxidation, thereby realizing the synchronous production of hydrogen. Compared with the traditional hydrogen production by electrolysis of water, the hydrogen production process of the present invention does not require electricity consumption, and can generate electricity to power external loads. The battery achieves a high output power density (173.5mW / cm 2 ), higher Faradaic efficiency (close to 100%) and faster hydrogen production rate (1.96mmol / cm 2 / h), which is at the leading level in existing research.

[0051] 2. In the battery constructed with the electrocatalyst prepared by the present invention, the biomass-derived aldehyde at the anode is oxidized into the corresponding acid while generating electricity. This process is carried out at room temperature and normal pressure, and the reaction is flexible and controllable. The existing reaction technology for oxidizing aldehydes into acids often uses air and oxygen under harsh conditions of high temperature and high pressure, or uses expensive oxidants for oxidation. Compared with the above traditional technologies, the present invention has higher safety and economy. And this low-potential aldehyde oxidation reaction of the present invention almost avoids competition with OER, greatly improving the Faraday efficiency (close to 100%). BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The linear sweep voltammetry curves of different types of copper-based catalysts used for electrocatalytic oxidation of benzaldehyde in Example 1 are shown.

[0053] Figure 2 Example 2 Ag-Cu at different potentials x (a) Conversion rate and (b) Faradaic efficiency of hydrogen production for O / CF electrocatalytic conversion of benzaldehyde.

[0054] Figure 3 Example 3 is based on Ag-Cux In situ differential electrochemical mass spectrometry of O / CF electrocatalytic conversion of benzaldehyde and the corresponding potential and current signal diagrams.

[0055] Figure 4 Example 4 is based on Ag-Cu x Linear sweep voltammetric curves of O / CF electrocatalytic conversion of benzaldehyde, furfural, p-anisaldehyde, and 3,4-dimethoxybenzaldehyde.

[0056] Figure 5 Example 5 is based on Ag-Cu x Current density-voltage-output power density plot of the biomass-derived aldehyde fuel cell with O / CF.

[0057] Figure 6 Example 6 is based on Ag-Cu x Time-current density-hydrogen production plot of the biomass-derived aldehyde fuel cell for O / CF.

[0058] Figure 7 The linear sweep voltammetry curves of different Ru-doped copper-based catalysts of Example 7, Comparative Example 1 and Comparative Example 2 for electrocatalytic oxidation of benzaldehyde. DETAILED DESCRIPTION

[0059] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0060] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0061] Example 1: Preparation of a copper-based electrocatalyst for the oxidation of biomass-derived aldehydes

[0062] 1. Preparation of copper-based electrocatalysts: (1) The copper foam was ultrasonically washed with acetone, 3 mol / L HCl solution, anhydrous ethanol and deionized water in turn, and the washing time was 10 min each. This material was recorded as CF. (2) Copper nanoparticles were loaded on the copper foam support by electrodeposition. The electrodeposition process was carried out in a three-electrode electrolytic cell (working electrode was CF, reference electrode was Ag / AgCl, and counter electrode was graphite rod) with a constant current of -20 mA / cm 2, lasting 1000s, the electrolyte is 0.5mol / L CuSO4 solution (the solution also contains 0.1mol / L ethanol and 0.2mol / L H2SO4). This material is recorded as Cu / CF. (3) Cyclic voltammetry (CV) activation is used to reconstruct the surface of the material and increase the electrochemical reaction active area. CV activation is carried out in a three-electrode electrolytic cell (the working electrode is Cu / CF, the reference electrode is Hg / HgO, the counter electrode is a graphite rod, and the electrolyte is 1mol / L KOH solution), and the scanning range is -0.1~1.2V RHE , the scan rate was 5mV / s, and the cycle was 10 cycles. After completing the CV activation, electrochemical reduction was carried out in the above three-electrode system at a constant potential of -0.3V RHE , the reduction time is 600s. This material is recorded as Cu x O / CF. (4) Cu x O / CF was placed in a 0.5mmol / L AgNO3 solution and stirred for 45min to dope Ag into the material. Then, electrochemical reduction was performed in a three-electrode system (the working electrode was the prepared material, the reference electrode was Hg / HgO, the counter electrode was a graphite rod, and the electrolyte was a 1mol / L KOH solution) at a constant potential of -0.3V. RHE , the reduction time is 300s. This material is recorded as Ag-Cu x O / CF.

[0063] 2. Performance test of copper-based catalyst for electrocatalytic oxidation of biomass-derived aldehydes: The test was carried out in a three-electrode system (working electrode is copper-based catalyst, reference electrode is Hg / HgO, counter electrode is graphite rod), the electrolyte is 1 mol / L KOH solution (containing 30 mmol / L benzaldehyde), and the scanning range is 0-0.5 V RHE The electrocatalytic performance was tested by linear sweep voltammetry. Figure 1 When the four copper-based catalysts prepared above were used as working electrodes, Ag-Cu x O / CF at 0~0.5V RHE The current response of is the largest, indicating that it has the highest electrocatalytic activity for the oxidation of aldehyde groups, while CF has almost no current response, indicating that it has no electrocatalytic activity. As the preparation steps proceed, the electrocatalytic activity of the copper-based catalyst gradually increases. This is because the electrodeposition of copper nanoparticles increases the specific surface area of ​​the material, CV activation increases the surface roughness of the material, and the electrochemical reduction process regulates the valence state of copper to zero-valent copper and monovalent copper with electrocatalytic activity. Silver doping can enhance the adsorption behavior of the catalyst on the reaction molecules to improve the electrocatalytic reaction activity.

[0064] Example 2: Ag-Cu x O / CF electrocatalytic conversion of benzaldehyde to produce aromatic acids and hydrogen simultaneously

[0065] Prepare Ag-Cu according to Example 1 x O / CF electrocatalyst is used for electrocatalytic conversion of benzaldehyde. The experiment of benzaldehyde electrocatalytic oxidation to produce hydrogen was carried out in an H-type electrolytic cell. The two cells were separated by a Nafion membrane. The anode electrolyte was 1 mol / L KOH solution (containing 30 mmol / L benzaldehyde) and the cathode electrolyte was 1 mol / L KOH solution. A three-electrode system was used, and the working electrode was Ag-Cu x O / CF, the reference electrode is Hg / HgO, and the counter electrode is a graphite rod. The reaction potential is controlled at 0.25V RHE , 0.3V RHE , 0.35V RHE , 0.4V RHE and 0.45V RHE The conversion rate was determined by high performance liquid chromatography, and the hydrogen production Faraday efficiency was determined by gas chromatography. The results are as follows Figure 2 As shown. Figure 2 (a) shows that at 0.4V RHE Previously, the conversion rate of benzaldehyde was close to 100%, but at 0.45V RHE When the potential is too high, the conversion rate of benzaldehyde is reduced to only 74.2%. This is because the catalyst is over-oxidized and more inactive divalent copper is generated. Figure 2 (b) shows that at 0.35V RHE Previously, the Faraday efficiency of hydrogen production was close to 100%, but at 0.4V RHE After that, the Faradaic efficiency of hydrogen production drops to only 60-77%. This is because benzaldehyde tends to be oxidized by a two-electron pathway (generating water instead of hydrogen) at a higher potential, and the production of hydrogen is inhibited.

[0066] Example 3: Ag-Cu x Mechanism of simultaneous hydrogen production from electrocatalytic conversion of aromatic aldehydes by O / CF

[0067] In order to verify the source of H in the hydrogen production from benzaldehyde oxidation, the present invention uses in situ differential electrochemical mass spectrometry to explore the reaction mechanism. x O / CF electrocatalyst is used to verify the mechanism of electrocatalytic conversion of benzaldehyde and simultaneous hydrogen production. A three-electrode system (working electrode is Ag-Cu x O / CF, reference electrode is Hg / HgO, counter electrode is graphite rod), electrolyte is 1mol / L KOD (containing 30mmol / L benzaldehyde, solvent is D2O). Set 0.35V RHEThe potential was raised (lasting 100s), the potential was paused (lasting 200s), and the above 300s was taken as one cycle, and the cycle was repeated 8 times (a total of 2400s), and the generated gas was measured in situ at the same time. The test results are as follows Figure 3 As shown, it can be seen that at 0.35V RHE When the H2 signal was detected, no HD and D2 signals were captured, which proved that the H2 came from the H2 in benzaldehyde, rather than from potassium hydroxide or water.

[0068] Example 4: Ag-Cu x Electrocatalytic performance of O / CF on different aromatic aldehyde substrates

[0069] Prepare Ag-Cu according to the method of Example 1 x O / CF electrocatalyst was used for the electrocatalytic conversion of four aromatic aldehydes, including benzaldehyde, furfural, p-anisaldehyde, and 3,4-dimethoxybenzaldehyde. Linear sweep voltammetry was performed in a three-electrode system (the working electrode was Ag-Cu x O / CF, the reference electrode is Hg / HgO, the counter electrode is a graphite rod), the electrolyte is 1 mol / L KOH solution (containing 30 mmol / L aromatic aldehyde), and the scanning range is 0~0.5V RHE The test results are as follows: Figure 4 As shown in the figure, the four aromatic aldehydes all have obvious current responses, indicating that Ag-Cu x O / CF has good electrocatalytic activity for different types of aldehyde compounds. The current response signals of the four aromatic aldehydes are benzaldehyde>furfural>p-methoxybenzaldehyde>3,4-dimethoxybenzaldehyde, which is because the electron-withdrawing / donating effect of the aromatic ring and substituent affects the reactivity of the aldehyde group.

[0070] Example 5: Construction and power generation performance testing of biomass-derived aldehyde fuel cells

[0071] Prepare Ag-Cu according to the method of Example 1 xO / CF electrocatalyst, which is used as the anode catalyst of the biomass-derived aldehyde fuel cell and loaded into the anode flow channel inside the battery. Carbon felt is loaded into the cathode flow channel inside the battery. The anode and cathode are separated by a Nafion membrane to prevent the battery from short-circuiting. The anode electrolyte is a 2mol / L KOH solution (containing 30mmol / L aromatic aldehydes), which is added to the anode tank. The cathode electrolyte is a 1mol / L FeCl3 acidic solution, which is added to the cathode tank. The anode electrolyte tank is connected to the anode inlet and outlet of the battery with a pipe, and the cathode tank is connected to the cathode inlet and outlet of the battery. The electrolyte circulates between the electrolyte tank and the battery through a pump, and the battery operating temperature is 25°C. The anode fuels of the four groups of batteries are benzaldehyde, furfural, p-methoxybenzaldehyde, and 3,4-dimethoxybenzaldehyde, respectively. At the same time, oxygen is introduced into the cathode tank at a flow rate of 20mL / min to achieve the regeneration of the cathode electrolyte. The power generation performance of the battery was tested by the scanning current method, and the results are as follows Figure 5 As shown, it can be seen that different types of biomass-derived aldehydes can be used in the fuel cell of the present invention to achieve power generation and hydrogen production, which proves the universality of the present invention.

[0072] Example 6: Hydrogen production rate test of biomass-derived aldehyde fuel cell

[0073] The biomass-derived aldehyde fuel cell constructed according to Example 5 was tested for its hydrogen production rate during long-term discharge using benzaldehyde as the anode fuel. The anode headspace gas was sampled (1 mL) at intervals of about 7 minutes and analyzed by gas chromatography to quantify the accumulated amount of hydrogen. The test results are shown in Figure 5. Figure 6 As shown, the battery has a high hydrogen production rate (about 1.96mmol / cm 2 / h).

[0074] Example 7: Preparation of Ru-doped copper-based electrocatalysts for efficient oxidation of biomass-derived aldehydes

[0075] 1. Preparation of Ru-doped copper-based electrocatalyst: The preparation steps are similar to those in Example 1. The difference is that the 0.5 mol / L AgNO3 solution in step (4) is replaced by a 0.5 mol / L RuCl3 solution, and the Cu x O / CF was placed in a 0.5 mmol / L RuCl3 solution and stirred for 45 min to dope Ru into the material. The remaining steps were the same as in Example 1. The obtained material was recorded as Ru-Cu x O / CF.

[0076] 2. Performance test of Ru-doped copper-based catalyst for electrocatalytic oxidation of biomass-derived aldehydes: The test was carried out in a three-electrode system (working electrode is copper-based catalyst, reference electrode is Hg / HgO, counter electrode is graphite rod), the electrolyte is 1 mol / L KOH solution (containing 30 mmol / L benzaldehyde), and the scanning range is 0-0.5 V RHE The electrocatalytic performance was tested by linear sweep voltammetry. Figure 7 Compared with the electrocatalysts prepared in Comparative Examples 1 and 2, it can be seen that Ru-Cu x O / CF at 0~0.5V RHE The current response of Ru-Cu x The electrocatalytic activity of O / CF-1 is second, and the electrocatalytic activity of Ru-Cu / CF is the lowest. This is because CV activation increases the surface roughness of the material, and the electrochemical reduction process adjusts the valence state of copper to zero-valent copper and monovalent copper with electrocatalytic activity. Ru doping can enhance the adsorption behavior of the catalyst on the reaction molecules to improve the electrocatalytic reaction activity. In addition, Example 7 is first electrodeposited, CV activated and electroreduced before Ru doping, while Comparative Example 2 is to dope Ru simultaneously during the electrodeposition process, and then perform CV activation and electroreduction. The method of Example 7 is better than Comparative Example 2, Ru-Cu x O / CF Ratio Ru-Cu x O / CF-1 has higher electrocatalytic activity.

[0077] Comparative Example 1: Preparation of unactivated copper-based catalyst by simultaneous Ru doping by electrodeposition

[0078] 1. Preparation of copper-based electrocatalysts: (1) The copper foam was ultrasonically washed with acetone, 3 mol / L HCl solution, anhydrous ethanol and deionized water in turn, and the washing time was 10 min each. This material was recorded as CF. (2) Copper nanoparticles were loaded on the copper foam support by electrodeposition and simultaneously doped with Ru. The electrodeposition process was carried out in a three-electrode electrolytic cell (working electrode was CF, reference electrode was Ag / AgCl, counter electrode was graphite rod), with a constant current of -20 mA / cm 2 , lasting 1000s, the electrolyte is 0.5mol / L CuSO4 solution (the solution also contains 0.1mol / L ethanol, 0.2mol / L H2SO4, and 0.5mol / L RuCl3). This material is recorded as Ru-Cu / CF.

[0079] 2. Performance test of copper-based catalyst for electrocatalytic oxidation of biomass-derived aldehydes: The test was carried out in a three-electrode system (working electrode is copper-based catalyst, reference electrode is Hg / HgO, counter electrode is graphite rod), the electrolyte is 1 mol / L KOH solution (containing 30 mmol / L benzaldehyde), and the scanning range is 0-0.5 V RHE The electrocatalytic performance was tested by linear sweep voltammetry. Figure 7 shown.

[0080] Comparative Example 2: Preparation of copper-based catalyst by simultaneous Ru doping by electrodeposition and CV activation

[0081] 1. Preparation of copper-based electrocatalyst: Steps (1) and (2) are the same as those in Comparative Example 1. (3) CV activation is used to reconstruct the surface of the material and increase the electrochemical reaction active area. CV activation is carried out in a three-electrode electrolytic cell (the working electrode is the prepared material, the reference electrode is Hg / HgO, the counter electrode is a graphite rod, and the electrolyte is a 1 mol / L KOH solution), with a scanning range of -0.1 to 1.2 V. RHE , the scan rate was 5mV / s, and the cycle was 10 cycles. After completing the CV activation, electrochemical reduction was carried out in the above three-electrode system at a constant potential of -0.3V RHE , the reduction time is 600s. This material is recorded as Ru-Cu x O / CF-1.

[0082] 2. Performance test of copper-based catalyst for electrocatalytic oxidation of biomass-derived aldehydes: The test was carried out in a three-electrode system (working electrode is copper-based catalyst, reference electrode is Hg / HgO, counter electrode is graphite rod), the electrolyte is 1 mol / L KOH solution (containing 30 mmol / L benzaldehyde), and the scanning range is 0-0.5 V RHE The electrocatalytic performance was tested by linear sweep voltammetry. Figure 7 shown.

[0083] Comparative Example 3: Furfural fuel cell based on H-PdCu ANs

[0084] H-PdCu ANs were prepared by reducing fresh K2Pd(CN)4 / CuCl2 cyano gel with NaBH4. First, 3.0mL 0.05mol / L K2Pd(CN)4 solution and 3.0mL 0.05mol / L CuCl2 solution were ultrasonically mixed uniformly at 30°C to produce a blue K2Pd(CN)4 / CuCl2 cyano gel, and freshly prepared NaBH4 aqueous solution (6mL, 0.033mg / mL) was added dropwise. The color of the gel immediately changed from blue to black. The solution was stirred continuously for 30min and then stirred continuously at 30°C for 9h. The derived black powder was repeatedly washed several times with 0.5mol / L H2SO4, water and ethanol, and then vacuum dried at 60°C overnight.

[0085] The biomass oxidation / oxygen reduction electrocatalytic system was assembled using H-PdCu ANs supported by carbon cloth as anode and cathode catalysts. 1mol / L KOH solution (containing 0.2mol / L furfural) was used as the anode electrolyte and 1mol / L KOH solution as the cathode electrolyte, and oxygen supply was required continuously. The power generation performance of the battery was tested by scanning current method, and the test results are listed in Table 1.

[0086] Comparative Example 4: Acid-base furfural fuel cell based on Pt-Cu

[0087] The Pt-Cu nanorods on copper foam were prepared by an electrochemical co-reduction method. The electroreduction process was carried out in a two-electrode system with a constant voltage of 3V for 30 minutes to obtain Cu(OH)2 loaded on copper foam, which served as the cathode. The platinum sheet was used as the anode, and 50mL of 1mol / L KOH / 0.1mmol / L H2PtCl6 mixed solution was used as the electrolyte. After the reaction, the Pt-Cu nanorods loaded on copper foam were washed with distilled water and then stored in ethanol.

[0088] 1.6 mg of commercial 20 wt% Pt / C powder was dispersed in a mixed solution containing 100 μL distilled water, 100 μL isopropanol and 10 μL 5 wt% Nafion solution, and ultrasonicated (40 kHz) for at least 1 h to form a uniform ink. The ink was then poured onto a piece of carbon paper (1 cm × 1 cm) under an infrared heating lamp.

[0089] Acid-base furfural fuel cells were assembled, in which Pt-Cu (1 cm × 1 cm) supported on copper foam and Pt / C (1 cm × 1 cm) supported on carbon paper were used as anode and cathode, respectively. +The exchange membrane was separated (previously converted by Nafion N115 PEM in 1mol / LKOH solution at 60°C). The cathode electrolyte was 1mol / L H2SO4, and the anolyte was 1mol / L KOH / 0.2mol / L furfural, with a peristaltic pump controlling the flow rate at 150mL / min. Two pieces of TA1 titanium metal, engraved with a single serpentine flow channel, were used as bipolar plates. The power generation performance of the battery was tested by the scanning current method, and the test results are listed in Table 1.

[0090] Comparative Example 5: Lignin fuel cell based on CoS@NF

[0091] CoS@NF was prepared by electrochemical deposition. The nickel foam was cut into 2.5×2.5 cm 2 As the working electrode. Before electrochemical deposition, ultrasonic washing was performed with dilute hydrochloric acid, anhydrous ethanol and ultrapure water in sequence. In order to prepare the CoS@NF anode, 50 ml of a mixed aqueous solution containing 2.5 mmol / L CoSO4·7H2O and 25 mmol / L thiourea was prepared. Electrochemical deposition was carried out using a three-electrode system, in which nickel foam was used as the working electrode, and Ag / AgCl and Pt mesh were used as the reference electrode and counter electrode, respectively. Electrochemical deposition was carried out at a constant potential of -1.0 V (relative to Ag / AgCl) for 30 min.

[0092] The lignin fuel cell consists of two graphite bipolar plates and a square flow chamber (20 mm wide × 20 mm long × 2 mm deep) and two copper plates as current collectors. The square flow chamber is filled with nickel foam (anode) and carbon felt (cathode). A Nafion 117 membrane is placed between the two graphite plates. The anolyte and cathode electrolyte enter and exit the square flow chamber through a peristaltic pump. 100 mg of lignin was dissolved in 50 mL of 3 mol / L KOH solution to obtain a lignin solution with a concentration of 2 g / L as the anolyte. 0.37 mol / L (VO2)2SO4 solution was used as the cathode electrolyte. The power generation performance of the battery was tested by the scanning current method, and the test results are listed in Table 1.

[0093] Comparative Example 6: Furfural fuel cell based on Ag2O@Ni foam

[0094] Ag2O@Ni foam was prepared by spraying silver oxide powder on nickel foam. 100 mg of Ag2O powder, 10 mg of PVDF and 10 mg of carbon powder were weighed and then mixed in an agate mortar. Then 1 mL of N-methylpyrrolidone was added and the mixture was ground for 1 h. The obtained slurry was then evenly coated on 3 pre-cut 1 cm × 1 cm pieces of nickel foam and placed in an oven to dry at 70 °C overnight. The Ag2O loading of the prepared Ag2O@Ni foam was about 33 mg / cm 2 .

[0095] The fuel cell mainly consists of two graphite plates (with a 1 cm × 1 cm square chamber engraved in the middle) and two conductive copper plates. Ag2O@Ni foam and carbon felt are embedded in the square chamber of the graphite plate as anode and cathode, respectively. The Nafion 115 membrane is sandwiched between the two graphite plates. By connecting the battery device to external anode and cathode containers for electrolyte storage and redox reactions, the furfural fuel cell can generate electricity and oxidize furfural to produce furanic acid. The electrolyte flows between the square chamber of the graphite plate and the external electrolyte storage container through a peristaltic pump at a flow rate of 98 mL / min. The electrolyte storage container is placed in a water bath to maintain the temperature (40 ° C), and the graphite plate is heated to the test temperature (40 ° C) by an electric heating rod. The cathode electrolyte and the anolyte are both 30 mL. O2 is continuously introduced into the cathode electrolyte to receive the electrons transferred by ABTS and laccase. The power generation performance of the battery was tested by scanning current method, and the test results are listed in Table 1.

[0096] Comparative Example 7: Furfural fuel cell based on Rh1Cu

[0097] A piece of copper foam (3cm×4cm) was calcined at 350℃ for 2h with a heating rate of 5℃ / min. Then, in a two-electrode system, nickel foam (3cm×4cm) was used as the anode and electrochemically reduced at a constant -3.0V for 30min in a 1mol / L KOH solution to obtain a copper electrocatalyst. A piece of copper electrocatalyst (3cm×4cm) was immersed in 100mL of an aqueous solution containing 25μmol RhCl3 and stirred at 500rpm for 20min to cause a replacement reaction to obtain a Rh1Cu electrocatalyst.

[0098] Co 1-x Ni x(OH)2 was prepared by electrodeposition in a three-electrode system, with 50 mL of 0.1 mol / L Ni(NO3)2·6H2O / Co(NO3)2·6H2O mixed solution as the electrolyte and Ag / AgCl as the reference electrode. Before use, the nickel foam was ultrasonically cleaned in 1 mol / L HCl solution, ethanol, and deionized water for 15 min. In order to prepare high mass loading (~50 mg / cm 2 ) electrodes, and multiple consecutive electrodepositions were performed, using two pieces of nickel foam of the same size (2.5 cm × 4 cm) as the working electrode and the counter electrode. 2 Under the conditions of , the electrodeposition was carried out 4 times, each time for 3000 s. In order to achieve uniform deposition, the electrode was inverted and the electrolyte was renewed in each electrodeposition process. After electrodeposition, the electrode was washed with deionized water to remove residual metal ions. Then, the obtained Co 1-x Ni x The (OH)2 electrode was activated by constant current (100 mA) charge and discharge (5 cycles).

[0099] Construction based on Rh1Cu(-)‖Co 0.2 Ni 0.8 (OH)2(+) furfural fuel cell. A piece of Rh1Cu catalyst was cut into 1.5cm 2 , pressed into a 2cm×2cm nickel foam. 0.2 Ni 0.8 (OH)2 (2 cm × 2 cm) electrode (mass loading ~50 mg / cm 2 ) as the cathode and clamped with two clean pieces of nickel foam of the same size to prevent the electrode material from falling off. Before assembly, the Rh1Cu catalyst was heated at -1.0V Hg / HgO Electroreduction was performed in 1 mol / L KOH solution for 300 s to remove the oxides that may have formed on the catalyst surface. Then, the Rh1Cu catalyst, Nafion 117 membrane and Co 0.2 Ni 0.8 (OH)2 is stacked layer by layer and pressed tightly. The flow channel area is 4cm 2 . The electrolyte was circulated by a peristaltic pump. The cathode electrolyte was a 1mol / L KOH solution with a flow rate of 15mL / min. 2mol / L KOH (15mL / min) and 0.2mol / L furfural (15mL / min) flowed through a three-way valve to synthesize an anolyte (1mol / LKOH+0.1mol / L furfural) with a flow rate of 30mL / min. The power generation performance of the battery was tested by the scanning current method, and the test results are listed in Table 1.

[0100] Comparative Example 8: Alkali lignin fuel cell based on CoS@Ni foam

[0101] The method of Comparative Example 5 was used to prepare CoS@Ni foam.

[0102] The battery body is composed of two graphite plates as anode and cathode, and a copper plate is mounted on the graphite plate as a current collector. A square flow chamber (1 cm wide × 1 cm long × 0.2 cm deep) is engraved in the middle of each graphite plate. On the anode side, the prepared CoS@Ni foam is cut into 1 cm × 1 cm size and filled into the flow chamber. In the flow chamber on the cathode side, carbon foam is filled. The Nafion 115 membrane is sandwiched between the two graphite plates to separate the anode and cathode. Two containers containing anolyte and cathode electrolyte (called anode reactor and cathode reactor) are connected to the flow chamber through pipes. The electrolyte is pumped into the battery and then circulated back to the reactor. The graphite plate is heated to the test temperature (40°C) with an electric heating rod. The power generation performance of the battery was tested by the scanning current method, and the test results are listed in Table 1.

[0103] Table 1 is a comprehensive comparison of the above embodiments and comparative examples in terms of operating temperature, whether hydrogen is produced, maximum power density, etc.

[0104] Table 1 Comprehensive comparison of various biomass fuel cell systems

[0105]

[0106] Comparing all the examples and comparative examples, it can be seen that the battery with the best power generation performance is the biomass-derived aldehyde fuel cell system constructed using benzaldehyde as raw material in Example 5, with a maximum power density of 173.5 mW / cm at room temperature. 2 , much higher than comparative examples 3 to 8. In addition, the biomass-derived aldehyde fuel cell of the present invention can use a variety of aldehyde compounds as anode fuels, and can obtain excellent output power density and achieve synchronous hydrogen production, further verifying the universality of the present invention. When furfural, p-methoxybenzaldehyde, and 3,4-dimethoxybenzaldehyde are used as anode fuels, the maximum power density at room temperature can reach 162.9 mW / cm 2 、138.5mW / cm 2 、104.9mW / cm 2 The differences in the electricity generation performance of different aldehyde compounds are due to the differences in the electron donating / withdrawing effects of the aromatic ring and substituents.

[0107] It can be seen that the present invention prepares an electrocatalyst (Ag-Cu xO / CF) to build a biomass-derived aldehyde fuel cell that can simultaneously generate electricity and hydrogen. The battery achieved a high output power density (173.5mW / cm 2 ), which is at the leading level in existing research. In addition, while generating electricity, the biomass-derived aldehydes at the anode are oxidized into corresponding carboxylic acid compounds. This process is carried out at room temperature and pressure, and the reaction is flexible and controllable. Compared with traditional aldehyde oxidation technology, it has higher safety and economy.

[0108] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an electrocatalyst, It is characterized in that The following steps are involved: (1) preparing at least one of copper, silver and gold nanoparticles on a substrate by electrodeposition to obtain a substrate loaded with nanoparticles; (2) activating the substrate loaded with the nanoparticles in step (1) by cyclic voltammetry, and then performing electrochemical reduction or reducing agent reduction to obtain a substrate loaded with metal oxide nanoparticles; The metal oxide nanoparticles are metal oxides corresponding to at least one element of copper, silver and gold; (3) doping the substrate loaded with metal oxide nanoparticles in step (2) with metal elements and then performing electrochemical reduction or reducing agent reduction to obtain a substrate loaded with metal elements doped with metal oxide nanoparticles, i.e., an electrocatalyst; The metal element doped therein is different from the metal element in the metal oxide nanoparticles.

2. An electrocatalyst according to claim 1, It is characterized in that The doped metal element in step (3) is at least one of Ag, Ru, Au, Pd, Pt, Fe and Co; The electrochemical reduction in step (3) is carried out in a three-electrode system, wherein the constant potential is -3.0 to 0.4 V. RHE , the restoration time is 10~3600s; The electrolyte of the three-electrode system is KOH, NaOH, Na 2 CO 3 、NaHCO 3 , K 2 CO 3 and KHCO 3 At least one of the following, with a concentration of 0.05 to 5 mol / L; The reducing agent in step (3) is NaBH 4 , LiBH 4 and Zn(BH 4 ) 2 At least one of the following; the specific method is to dope the substrate loaded with metal oxide nanoparticles in step (2) with metal elements and then place it in a 0.001 to 3 mol / L reducing agent aqueous solution for immersion reduction, and the reduction time is 10 to 3600 s; The method of doping the metal element in step (3) is as follows: placing the substrate loaded with metal oxide nanoparticles in a 0.05-50 mmol / L metal salt solution for 10-240 min to dope the metal element into the metal oxide nanoparticles; The metal salt solution is AgNO 3 、RuCl 3 、AuBr 3 , PdCl 2 、Pt(NO 3 ) 2 、Fe(NO 3 ) 3 and Co(NO 3 ) 2 At least one of .

3. An electrocatalyst according to claim 1, It is characterized in that The cyclic voltammetry activation in step (2) is carried out in a three-electrode system with a scanning range of -1.0 to 2.0 V. RHE , scanning speed is 0.5~100mV / s, and the cycle is 1~100 times; The electrolyte for cyclic voltammetry activation in step (2) is KOH, NaOH, Na 2 CO 3 、NaHCO 3 , K 2 CO 3 and KHCO 3 At least one of the following, with a concentration of 0.05 to 5 mol / L; The electrochemical reduction in step (2) is carried out in a three-electrode system activated by cyclic voltammetry, wherein the constant potential is -3.0 to 0.4 V. RHE , the restoration time is 10~3600s; The reducing agent in step (2) is NaBH 4 , LiBH 4 and Zn(BH 4 ) 2 At least one of the following: specifically, placing the substrate loaded with nanoparticles after cyclic voltammetry activation in a 0.001 to 3 mol / L reducing agent aqueous solution for immersion reduction, and the reduction time is 10 to 5000 s.

4. An electrocatalyst according to claim 1, It is characterized in that The substrate in step (1) is at least one of foamed copper, foamed nickel, foamed zinc, foamed aluminum, carbon felt, carbon paper and carbon cloth; The electrolyte used in the electrodeposition method in step (1) is CuSO 4 , CuCl 2 、Cu(NO 3 ) 2 AgNO 3 and AuBr 3 At least one of the following, with a concentration of 0.01 to 3 mol / L; The electrolyte also contains 0.001-2 mol / L ethanol and 0.001-4 mol / L H 2 SO 4 ; The electrodeposition process in step (1) is carried out in a three-electrode system, wherein the constant current is -500 to -1 mA / cm 2 The electrodeposition time is 10 to 5000 s.

5. An electrocatalyst prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the electrocatalyst according to claim 5 in a fuel cell.

7. A biomass-derived aldehyde fuel cell that co-produces electricity and hydrogen, It is characterized in that including an anode, a cathode, an anolyte, a catholyte, a separator and a conductor; The anode is loaded with the electrocatalyst according to claim 5; the anode electrolyte contains biomass-derived aldehydes at a concentration of 1 to 1000 mmol / L.

8. A biomass-derived aldehyde fuel cell for co-producing electricity and hydrogen according to claim 7, It is characterized in that The biomass-derived aldehyde in the anolyte is at least one of benzaldehyde, p-methoxybenzaldehyde, 3,4-dimethoxybenzaldehyde, furfural, 5-hydroxymethylfurfural and formaldehyde; the concentration of the biomass-derived aldehyde in the anolyte is 1 to 1000 mmol / L; The alkali in the anode electrolyte is at least one of NaOH, KOH and ammonia water, and the concentration of the alkali is 0.001 to 8 mol / L; The operating temperature of the biomass-derived aldehyde fuel cell is 5 to 98°C; The electrocatalyst according to claim 5 is loaded as an anode catalyst in the anode flow channel inside the battery.

9. A biomass-derived aldehyde fuel cell for co-producing electricity and hydrogen according to claim 7, It is characterized in that The cathode electrolyte includes a ferric iron salt with a concentration of 0.01 to 4 mol / L, an acid solution with a concentration of 0.01 to 6 mol / L, and a cathode regeneration oxidant; The ferric iron salt is at least one of ferric chloride, ferric sulfate and ferric nitrate; the acid solution is at least one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution; the cathode regeneration oxidant is at least one of nitric acid, oxygen, hydrogen peroxide and potassium permanganate; When the cathode regeneration oxidant is nitric acid, its concentration in the cathode electrolyte is 0.01 to 8 mol / L; when the cathode regeneration oxidant is oxygen, its flow rate is 10 to 100 mL / min; when the cathode regeneration oxidant is hydrogen peroxide, its concentration is 0.2 to 10 mol / L; when the cathode regeneration oxidant is potassium permanganate, its concentration is 0.01 to 0.5 mol / L.

10. A biomass-derived aldehyde fuel cell for co-producing electricity and hydrogen according to claim 7, It is characterized in that The anode and cathode are separated by a diaphragm to form an anode chamber filled with an anolyte and a cathode chamber filled with a catholyte; The diaphragm is a Nafion membrane; The electrode material in the cathode is carbon felt; The biomass-derived aldehyde fuel cell also includes a circulation pump, through which the anolyte and the cathode electrolyte are transported to the anode and cathode respectively; The wires connect the anode and cathode to an external circuit respectively.

Citation Information

Patent Citations

  • Chargeable and dischargeable biomass battery

    CN116344885A

  • Surface-oxidized nickel-copper alloy catalyst and preparation and application thereof

    CN118086958A

  • Electrode catalyst, method for producing the same, and method for producing hydrogen

    JP2021070864A

  • Anodic catalysts consisting of noble metals spontaneously deposited onto nanostructured catalysts composed of transition metals, their synthesis and use in fuel cells

    WO2008009742A1